Metals Streaming and Royalty Financing: A Framework for Assessing Mining Sector Financial Benefit–Sharing Implications for Governments - Ekpen J. Omonbude (Revue Internationale de Politique de Développement)
This chapter offers a simplified approach to assessing the potential impact of metals streaming and royalty financing on government revenues. Subject to the availability and quality of information, a revenue impact ratio can be determined by comparing the potential revenues to the government from more traditional forms of financing with potential revenues to the government from metals streaming or royalty financing.The chapter considers the key features, advantages, and disadvantages of these alternative funding options for mining projects, and then develops an illustrative model to demonstrate their potential impact on government revenues. This forms the basis on which to identify the key challenges, and the policy considerations when addressing them.While metals streaming provides upfront capital and a potential hedge against price risk for producers, it could also limit the upside potential for both the mining company and the host government. On the other hand, royalty financing offers stable income streams and diversification opportunities for investors but may lack direct exposure to metal price increases.The ultimate risk faced by resource-rich governments as a result of an increase in the use of metals streaming and royalty financing arrangements is a suboptimal share of the potential benefits that will accrue from the mining operations. Specifically, the risk is of a reduction in taxable income and royalty revenue.At the heart of the policy considerations pertaining to resolving these challenges and risks is reducing information asymmetry between the government, the mining company and the streaming or royalty company. One important way to do this is to strengthen tax legislation and enforcement mechanisms. Implementing anti-avoidance rules, such as interest limitation rules, can limit the ability of metals streaming and royalty financing companies to exploit tax and other loopholes. Other features with which to strengthen the legislation include clear minerals pricing rules, and clearer provisions regarding withholding taxes.